Analyzing DevOps Teaching Strategies: An Initial Study - Ferino, Samuel; Fernandes, Marcelo; Fernandes, Anny; Kulesza, Uirá; Aranha, Eduardo; Treude, Christoph (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
DevOps refers to a set of practices that integrate software development and operations with the primary aim to enable the continuous delivery of high-quality software. DevOps has also promoted several challenges to software engineering teaching. In this paper, we present a preliminary study that analyzes existing teaching strategies reported in the literature. Our findings indicate a set of approaches highlighting the use of environments to support teaching. Our work also investigates how these environments can contribute to address existing challenges and recommendations of DevOps teaching.